IInfluence of calcined nanomagnesia on the structure and dielectric properties of polypropylene/ethylene-octene copolymer blend - Kamarudin, Siti Noorhazirah; Kwan, Yiew Lau; Ahmad, Noor Azlinda; Azrin, Nur Azalia; Rahim, Nor Hidayah; Chee, Wei Tan; Kuan, Yong Ching; Abdul Ghani, Ahmad Basri; Nor Arifin, Nur Amira (IOP Publishing Ltd., 2025)
Polymer blends have attracted significant research interest due to their potential use as power cable insulating materials. Specifically, polypropylene (PP) blends offer improved dielectric properties over conventional crosslinked polyethylene insulating materials attributable to PP’s high melting temperatures, hence high rated voltages. Despite numerous promising findings have been reported regarding the potential application of PP blends as power cable insulating materials, there have been relatively less investigations into the dielectric effects of incorporating nanofillers into PP blends. The current work therefore explores the influence of calcined magnesia (MgO) nanofiller on the structure and dielectric properties of PP blended with ethylene-octene copolymer (EOC). Nanofiller-wise, calcination of MgO does not significantly affect the structure of MgO, albeit that water-related molecules are removed from MgO. Upon adding the calcined MgO to the PP/EOC blend, the breakdown performance of the PP/EOC/MgO blend nanocomposites becomes jeopardized, especially under the direct current field. This is primarily attributed to the presence of residue water molecules within the PP/EOC/MgO blend nanocomposites, even after MgO calcination. Although the addition of the calcined MgO to the PP blend does not result in favorable dielectric properties, the findings suggest that nanostructuration of PP blends could be further explored to pave the way for the development of nanostructured PP blends for use in advanced power cable insulation applications.